Film noir - Luhr, William (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
Film Noir offers new perspectives on this highly popular and influential film genre, providing a useful overview of its historical evolution and the many critical debates over its stylistic elements. Brings together a range of perspectives on a topic that has been much discussed but remains notoriously ill-defined. Traces the historical development of the genre, usefully exploring the relations between the films of the 1940s and 1950s that established the ""noir"" universe and the more recent films in which it has been frequently revived. Employs a clear and intelligent writing style that makes this the perfect introduction to the genre. Offers a thorough and engaging analysis of this popular area of film studies for students and scholars. Presents an in-depth analysis of six key films, each exemplifying important trends of film noir: Murder, My Sweet; Out of the Past; Kiss Me Deadly; The Long Goodbye; Chinatown; and Seven.
Introduction -- Historical overview -- Critical overview -- Murder my sweet -- Out of the past -- Kiss me deadly -- The long goodbye -- Chinatown -- Seven : continuity with film noir -- Afterword.
Includes bibliographical references and index.
Print version record.
Keywords: Film noir -- United States -- History and criticism; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; Film noir; United States; Electronic books; Criticism, interpretation, etc